Study on the Performance of a Solar Heating System with Seasonal and Cascade Thermal-Energy Storage - Xiuyan Yue; Yujie Xu; Xuezhi Zhou; Dehou Xu; Haisheng Chen (Energies, 2022)
Seasonal solar thermal-energy storage systems used for space heating applications is a promising technology to reduce greenhouse gas emissions. A novel solar heating system with seasonal and cascade thermal-energy storage based on zeolite water is proposed in this study. The system’s efficiency is improved through cascade storage and the release of solar energy. The energy storage density is improved through the deep coupling of daily energy storage and cross-seasonal energy storage. A mathematical model of the system-performance analysis is established. The system performances in the non-heating and heating seasons and throughout the year are analyzed by considering the Chifeng City of China as an application case. The results indicate that the average collection efficiency of the proposed system is 2.88% higher in the non-heating season and 7.4% higher in the heating season than that of the reference system. Furthermore, the utilization efficiency of the proposed system is 37.16%, which is 3.26% higher than that of the reference system. Further, the proposed system has a supply heat of 2135 GJ in the heating season, which is 9.66% higher than the reference system. This study provides a solution for the highly efficient solar energy utilization for large-scale space-heating applications.